Development of Natural Fibre-Reinforced Polymer Composites Ballistic Helmet Using Concurrent Engineering Approach: A Brief Review - Asyraf M.Z.; Suriani M.J.; Ruzaidi C.M.; Khalina A.; Ilyas R.A.; Asyraf M.R.M.; Syamsir A.; Azmi A.; Mohamed A. (MDPI, 2023)
composite; design method; engineering; manufacturing; polymer; product development